2020
DOI: 10.1186/s12889-020-8416-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health vs. non-health goals on individuals’ lifestyle program choices: a discrete choice experiment approach

Abstract: Background: Goals play an important role in the choices that individuals make. Yet, there is no clear approach of how to incorporate goals in discrete choice experiments. In this paper, we present such an approach and illustrate it in the context of lifestyle programs. Furthermore, we investigate how non-health vs. health goals affect individuals' choices via non-goal attributes. Methods: We used an unlabeled discrete choice experiment about lifestyle programs based on two experimental conditions in which eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Our results are not directly comparable, because we focused specifically on diet-based interventions, and we found that type of diet was the leading driver of preferences. In two studies ( 4 , 5 ), weight loss was more important than type of diet (although the diet options were unspecific [i.e., “restrictive,” “flexible,” and “no diet”]). Other studies (e.g., Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are not directly comparable, because we focused specifically on diet-based interventions, and we found that type of diet was the leading driver of preferences. In two studies ( 4 , 5 ), weight loss was more important than type of diet (although the diet options were unspecific [i.e., “restrictive,” “flexible,” and “no diet”]). Other studies (e.g., Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, psychologists emphasize the importance of goals and goal pursuit for understanding consumer choices (e.g., Kopetz et al 2012). Research substantiated the importance of goal pursuit for health-related behavior (Benning et al 2020). We argue that investigating the interplay of selfquantification and health and fitness goal pursuit motivation furthers our understanding of lasting smartwatch use.…”
Section: Introductionmentioning
confidence: 83%
“…Risk aversion preference and relative importance weights suggests risk reduction is perceived as the participants' goal in weighing choices. Therefore, allowing that 54% of CRC cases in the UK are preventable 92 , if action were taken to enhance individual agency in this known risk group, by developing the awareness of the association between adenoma removal, ongoing surveillance, CRC and lifestylerelated cancer risks, patient outcomes could be further optimized relative to the status-quo, in keeping with a risk reduction goal 93 .…”
Section: Discussionmentioning
confidence: 99%